Design and Optimization of Sesamol Nanosuspensions to Potentiate the Anti-Tumor Activity of Epirubicin against Ehrlich Solid Carcinoma-Bearing Mice - Kholoud A. Elzanaty; Gamal A. Omran; Ehab Kotb Elmahallawy; Ashraf Albrakati; Ayman A. Saleh; Naief Dahran; Alaa S. Alhegaili; Ahmad Salahuddin; Heba Abd-; Ahmed Noreldin; Tarek M. Okda (MDPI AG, 2024)
There is a growing interest in discovering natural sources of anti-cancer drugs. Sesamol (SES) is a phenolic compound with antitumor effects. The present study aimed to investigate the anticancer properties of SES and its nano-suspensions (SES-NS) combined with Epirubicin (EPI) in breast cancer (BC) using mice bearing a solid Ehrlich tumor. The study involved 35 female albino mice and investigated the effects of SES and EPI on tumor growth, proliferation, apoptosis, autophagy, angiogenesis, and oxidative stress. Methods including ELISA, qRT-PCR, and immunohistochemistry were utilized. The findings revealed reductions in tumor growth and proliferation using SES either alone or combined and evidenced by decreased AKT (AKT Serine/Threonine kinase1) levels, angiogenesis indicated by lower levels of VEGFR (vascular endothelial growth factor), and apoptosis demonstrated by elevated caspase3 and BAX levels. Furthermore, autophagy increased and was indicated by increased levels of beclin1 and lc3, along with decreased oxidative stress as evidenced by elevated TAC (total antioxidant capacity) and reduced MDA (malondialdehyde) levels. Interestingly, SES-NS demonstrated more significant effects at lower doses. In summary, this study underscores the potential of SES as a promising agent for BC treatment. Moreover, SES-NS potentiated the beneficial effects of EPI while mitigating its adverse effects.